NUMMULITE BIOSTRATIGRAPHY AT THE MIDDLE/UPPER EOCENE BOUNDARY IN THE NORTHERN MEDITERRANEAN AREA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
Some larger  foraminiferal assemblages (mostly nummulitids) near the Middle/Upper Eocene boundary have been investigated. Sections of the Veneto area (Berici and Lessini Mts., northern Italy) were studied and compared with others of the same age from Spain (Ebro basin) and Romania (Cluj-Napoca). In the Veneto area the results allow to split the upper Middle Eocene Nummulites brongniarti Zone into two biozones: a lower N. lyelli Zone and an upper N. biedai Zone. The N. aff. fahianìi Zone is here renamed N. variolarias/incrassatus Zone. This subdivision can also  be recognized in Spain and Romania. According to the current conceptions,  the base of the Priabonian (= Upper Eocene) could correspond either to the base of the N. fabianii s.s. Zone or to the base of the N. vaiolarius/ incrassatas Zone. Anyway, the Mossano succession could be a potential Globai Stratotype Section and Point for the base of the Priabonian.
Keywords: Biostratigraphy; Nummulites; Middle/Upper Eocene boundary; Northern Mediterranean.